P-T-t paths of garnets from the Nanga Parbat-Haramosh Massif, the Kohistan and the Ladakh island arc terranes, northern Pakistan - Khattak, Muhammad U.K.; Stakes, Debra S.; Shervais, John W. (Journal of Himalayan Earth Sciences, 1995)
Metamorphic rocks of the Nanga Parbat-Haramosh Massif (NPHM) are represented by an intercalated sequence of para- and orthogneisses, with minor metabasites, calcsilicate rocks, and post-metamorphic pegmatite dikes. Garnets from two gar-bio-sill paragneisses in the NPHM are characterized by three distinct textural zones: (1) an inclusion-free core, (2) an inclusion-filled intermediate zone, and (3) inclusion-free rims. These garnets are characterized by distinct chemical zoning profiles from core to rim. Equilibration temperatures for these garnets, calculated with the garnet-biotite geothermometer, are 650oC in the inclusion-free core, 725oC in the inclusion-filled intermediate zone, and 500oC in the inclusion-free rim. Garnets in a paragneiss adjacent to the Astak Fault Zone and the Ladakh arc terrane are inclusion-free throughout, and have nearly flat, unzoned chemical profiles. Equilibration temperatures for these annealed garnets are 700-684oC, with thin rims 610oC. The dominance of relatively high equilibration temperatures in all of these garnets is confirmed by oxygen isotope partitioning studies, which show that most garnet-quartz, feldspar-quartz, biotitequartz mineral pairs equilibrated at 700oC in the NPHM Khattak, 1995). The Ladakh arc terrane, east of the Astak Fault Zone, consists largely of meta-volcanic rocks, but also contains minor paragneiss horizons. Garnets found in gar-bio-sill paragneisses from the Ladakh arc terrane contain minor inclusions in the core but have inclusion-free rims. These show a sharp step-like change in chemistry at the boundary between core and rim, with relatively high temperatures in the inclusion-filled cores ( 720-650oC and lower temperature ( 580oC). The chemical zoning, P-T estimates, and the textural features of these garnets are interpreted as indicative of the tectonic history of the area. The flat chemical zoning indicates annealing (re-equilibration) of the garnets during or after the peak of upper amphibolite facies metamorphism. The occurrence of inclusions coincides with the preservation of the original growth zoning under dynamic, rapid growth conditions. The following tectonic history is proposed: (1) the inclusion-free core of the NPHM garnets may represent collision of the Indian plate with the Ladakh arc; (2) the higher temperature inclusion-filled intermediate zone in the NPHM garnets and the inclusion-filled core of the Ladakh garnets indicates growth during collision of the India-Ladakh package with the Asian plate; and (3) the outermost inclusion-free zones in garnets from both the terranes probably formed during unroofing/cooling. Annealed garnets of the NPHM adjacent to the Astak Fault Zone probably reflect heating by the hot base of the over-riding Ladakh arc.